[Just Nuts - Tobago, B.W.I.] - (:unkn) unknown (My University, 2009)
This is a picture of a labourer in front of a shed emptying a sack of coconuts onto a pile for processing. Affixed to the back of the postcard is a Trinidad and Tobago 4 cents stamp.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coconut palm--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Working class--Trinidad and Tobago